Management Practice of Cinnamomum tamala in Eladi VDC of Syangja, Nepal - Thapa, Mahendra Singh; K.C., Baburam (Himalayan Biodiversity, 2017)
Cinnamomum tamala is a moderate sized evergreen tree species which is used as spices in Indian subcontinent. In Nepal, it is found between 500- 2000 m above sea level. Its English name is Indian cassia lignea or Cinnamon. Leaves and bark of the species contain aromatic oil and are used as spices. The status and distribution of this species has less explored so this study has been carried out to assess the resource base and management practice at Eladi VDC of Syangja district. The researcher estimated the existing stand of Sinkauli, its annual increment, the annual allowable harvest, density, relative density, frequency, relative frequency and abundance along with its ethnobotanical uses. Community forests, National forest and private forest consisting of Sinkauli stands were inventoried based on the stratified random sampling. The scattered trees in the farmland and marginal land were enumerated and mesured. The measurement of DBH were stratified into different size groups at the interval of 5 cm DBH class and at 5 years interval of age classes. Altogether 98 trees were sampled from 0.14 ha area. For the measurement of fresh weight and air-dried weight of bark and foliage, thirty two sample trees representing the Sinkauli stand, were felled and measured. Data were analyzed by using different statistical tools like mean, diagrams, flowcharts, and pie chart. The density, relative density, frequency, relative frequency, abundance and growing stock are 13171, 55.34%, 100%, 11.7%, 13171, 700 trees/ha respectively. The air-dried weight to fresh weight ratio of bark of C. tamala is found to be 0.5210 and that of leaf is 0.5721. From this VDC, 345 trees of average age could be harvested with which 2944 kg bark and 2409 kg of leaves could be extracted annually. Based on the existing price at the local market, Rs 1177,60 from bark (RS 40/ Kg) and Rs 36130 from foliage (Rs 15/ Kg) could be earned annually. As people are less aware about the importance of C.tamala and the resource is dwindling from natural stand, the awareness program for its proper management, cooperation among different stakeholders, provision of economic market, and development of proper monitoring and evaluation program are recommended for the sustainable management of C.tamala stands.